ANALISIS PENULISAN RESEP UNTUK PASIEN PESERTA JAMINAN KESEHATAN NASIONAL PADA PUSKESMAS DI KOTA PADANG - Sadewa, Arendhika Sesa; Julizar, Jullizar; Usman, Elly; Ilmiawati, Cimi; Nurhayati, Nurhayati; Isrona, Laila (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Prescription contain information about medication that used to treat the diagnosis and prevent complications from patient. A doctor should refer to the principles of rational therapy and National Formularies (FORNAS) in accordance with Government Regulation No. 12 of 2013. A correct prescription will minimize the occurrence of medication errors that could endanger the patient's life. From some studies, there are still many prescriptions that doesn’t pass the standards. This study aimed to analyze the quality of the doctor’s prescription writing for National Health Insurance (JKN) patients at health centers in Padang city. This observational study was performed in the three health centers in September 2023. Sampling was done by proportional stratified random technique, where we obtained 378 prescriptions. Prescriptions were analyzed for accuracy and completeness according to the WHO’s Guide to Good Prescribing. Prescription analysis showed that prescriptio were mostly complete (74%), superscriptio were all complete (100%), inscriptio were mostly complete (67%), signatura were mainly complete (99%), subscriptio were partially complete (58%), pro were nearly complete (96%) and 88% of prescription confirmed with the FORNAS.  It is concluded that improvements are needed in prescription writing and using drugs that are registered on FORNAS.